Investigating Factors Associated With not Reporting Medical Errors From the Medical Team’S Point of View in Jahrom, Iran - Jahromi, Zohreh Badiyepeymaie (Glob J Health Sci, 2014)
BACKGROUND: medical errors as a problematic fact in healthcare systems can increase patient’s safety if reported. This article tried to determine several factors associated with not reporting medical errors from medical team’s points of view. METHODS: 300 staff working in different parts of educational hospitals affiliated to Jahrom University of Medical Sciences including nursing, midwifery, paramedical and medical groups participated in this descriptive study using census method (2013). Data collection was performed using a researcher-made questionnaire including 31 items regarding four areas: medical teams, managers, errors and patients. RESULTS: The mean score of factors related to errors, mangers, medical teams, and patients’ scope was 2.68 ± 0.79, 2.63 ± 0.72, 2.53 ± 0.66, 2.41 ± 0.87, respectively. In medical teams’ points of view, errors and managers were among the important factors for not reporting professional errors. The most important factors in professional errors were related to severity and emergency of errors (2.73 ± 0.97), and managers’ focus on wrongdoers instead of noticing systematic factors of errors (3.00 ± 1.01). In medical teams, fear of legal prosecution by patients or their relatives (2.87 ± .97), and in patients, unawareness of errors (2.67 ± 1.08) was reported as the most effective factors. CONCLUSION: Factors related to errors and managers were more important than other reasons. Therefore, educating medical teams on recognizing errors and managers’ proper reactions in case of occurring or reporting errors seem to be necessary.